The Role of Audit Quality in Moderating Political Connection and CFO Characteristics on Tax Aggresiveness - Syifa Amatullah Isymah (AFRE (Accounting and Financial Review), 2025)
This study aims to examine the role of audit quality in moderating the effect of political connection and CFO characteristics on tax aggressiveness. The population in this study consists of manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2018-2022. The sampling technique used is purposive sampling with a total 255 observational data from 51 sample companies. The results indicate that political connections has no effect on tax aggressiveness. The CFO characteristics that has a negative effect on tax aggressiveness are gender and education level while accounting expertise has no effect. The result also show audit quality unable to strengthen the effect of political connection and CFO gender on tax aggressiveness but able to weaken the impact of the CFO's education level and accounting expertise on tax aggressiveness. JEL Classification: H26; M41; J16. DOI: https://doi.org/10.26905/afr.v8i1.13794